Hambúrguer de frango incorporado com extrato de gengibre: características físico-químicas, tecnológicas e aceitação sensorial. - Maximo, Samira da Silva (2019)
The quality of meat and meat products is related to the properties of proteins. The use of proteolytic enzymes has been used to improve the physical-chemical and sensory characteristics of meat derivatives. In this context, the present study aimed to evaluate the effect of ginger extract in concentrations of 3%, 5%, 7% and 10% on chicken breast stored at 4ºC for 24 hours in the water retention capacity, protein solubility, myofibrillar fragmentation index and shear force. The effect of these extract concentrations on shear strength, myofibrillar fragmentation index, post-cooking weight loss and sensory acceptance of chicken hamburger was also evaluated by adding ginger extract as an ingredient. There was a tendency to decrease the water retention capacity and shear strength of chicken breasts with an increase in the concentration of ginger extract, while for the myofibrillar fragmentation index and myofibrillar and total protein solubility there was a significant increase in their values. Regarding hamburgers, there was a tendency to increase the myofibrillar fragmentation index and decrease in shear strength with the increase in the concentration of ginger extract. For the loss after cooking, the lowest observed value was 3% of extract tending to increase with the increase in the concentration of extract in the formulation. By the sensory acceptance test, all hamburgers had good acceptance for the flavor, softness, juiciness and overall impression attributes, with greater consumer acceptability for chicken hamburgers with 3% and 7% ginger extract. Therefore, the addition of ginger extract as a natural ingredient contributed to improving the quality and acceptance of the sensory attributes of the chicken burger. In chicken breast, it is also considered that the positive effects of its addition were more relevant than the decrease in the water holding capacity and, therefore, that it also contributed to the improvement of the meat quality.